BTK inhibition in primary central nervous system lymphoma: mechanisms, clinical efficacy, and future perspectives - Xing, Yurou; Zhao, Kejia; Zhang, Yi; Wang, Yongsheng (Frontiers in Oncology, 2024)
The prognosis of primary central nervous system lymphoma (PCNSL) patients is relatively poor, and there is currently no standard treatment plan. Most patients choose high-dose chemotherapy based on methotrexate. While traditional chemotherapy combined with biological therapy has achieved limited results, some patients still do not respond to treatment or cannot tolerate its toxicity and side effects. Bruton’s tyrosine kinase (BTK) is a key enzyme in B-cell receptor signaling, and its activation is critical for B-cell survival and proliferation. In recent years, BTK inhibitors have shown great potential in treating lymphomas derived from various B cells because of their strong targeting ability and relatively few side effects. They may also be a reasonable treatment choice for PCNSL. This article reviews the mechanism of action, clinical research, adverse reactions, and other issues of BTK inhibitors in treating PCNSL to provide a reference for individualized treatment of patients with PCNSL.